Challenges in teaching of English to pre-schoolers: a case study in Malaysian schools - Lotfie, Maskanah Mohammad; Md Zamin, Ainul Azmin; Mohamed Salleh, Rabiah Tul Adawiyah (IIUM Press, 2022)
his paperinvestigates the challenges preschool teachers facein an environment where they are expected to use English as a language of instruction alongside Malay, the national language. The researchers gathered information on the teachers’ educational background in teaching and training, their perceptions of the problems they face in facilitating the teaching and learning process of the children, as well as their suggestions on effectively overcoming the setbacks. In-depth online interviews were conducted, and data analysis was carried out using Atlas-ti. The results indicated that the teachers lack skills in teaching English due to the different bachelor’s degrees they obtained. However, this can be rectified if continuous training and development are offered, especially when there is a change in the syllabus. Apart from the teachers’ initiatives in tackling the various problems related to teaching, recommendations were made to encourage parents and school administrators to join forces in improving the quality of education. Teacher training needs to be further enhanced to ensure the effectiveness of implementing English as one of the instructional languages used in preschools. Students’ low level of proficiency in English is also a challenge faced by the teachers as well. Although technology is integrated into school, optimizing it in class can sometimes be difficult for teachers due to software issues